2023
DOI: 10.3390/ijms242015371
|View full text |Cite
|
Sign up to set email alerts
|

Proteins from Blackberry Seeds: Extraction, Osborne Isolate, Characteristics, Functional Properties, and Bioactivities

Shaoyi Wang,
Fengyi Zhao,
Wenlong Wu
et al.

Abstract: Blackberry fruit contains high levels of nutrients and phenolic compounds. Blackberry pomace accounts for 20~30% of its whole fruit during processing and is generally treated as fertilizer. Blackberry pomace has many seeds that contain carbohydrates, polyphenols, flavonoids, pectin, protein, and other bioactive nutrients. However, its functional properties and seed protein compositions have not been reported. We used a single-factor experiment, response surface, and Osborne isolate method to extract protein is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…Researchers determined that blackberry pomace contains a lot of seeds, and from these they obtained protein isolates, albumin, globulin, glutelin, and prolamin [51]. They found that albumin and globulin from blackberry seeds showed good oil holding capacity [51]. In this study, we also determined a strong positive correlation (r = 0.832, p ≤ 0.05) between the number of proteins and oil holding capacity (Table 4).…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Researchers determined that blackberry pomace contains a lot of seeds, and from these they obtained protein isolates, albumin, globulin, glutelin, and prolamin [51]. They found that albumin and globulin from blackberry seeds showed good oil holding capacity [51]. In this study, we also determined a strong positive correlation (r = 0.832, p ≤ 0.05) between the number of proteins and oil holding capacity (Table 4).…”
Section: Resultssupporting
confidence: 60%
“…Blackberry seeds contain bioactive components, such as carbohydrates, polyphenols, flavonoids, triterpenoids, pectins, and proteins. Researchers determined that blackberry pomace contains a lot of seeds, and from these they obtained protein isolates, albumin, globulin, glutelin, and prolamin [51]. They found that albumin and globulin from blackberry seeds showed good oil holding capacity [51].…”
Section: Resultsmentioning
confidence: 99%